Forcasting Natural Gas Consumption in Nigeria using the Modified Grey Model (MGM(1,1,⊗b)) - Samuel O. Obi; Imam Akeyede (African Scientific Reports, 2022)
Accurate prediction of the natural gas consumption in Nigeria is crucial to Gas management. This study utilizes the improved Grey model (MGM(1,1,⊗b)), which is an improvement of the modified Grey model (MGM(1,1)), to forecast the natural gas consumption of Nigeria for the year 2021 to 2025. A secondary data retrieved from the NNPC 2019 annual statistics bulletin was used to build a model for this prediction. Noting that MGM(1,1) model uses the Grey action quantity as a unique real number which do not reflect the uncertainty nature of Grey systems. A model (MGM(1,1,⊗b)) was developed such that it extends the MGM(1,1) model to retain the uncertainty nature of Grey systems. The new modified Grey model (MGM(1,1,⊗b)) was used to make prediction of the natural gas consumption of Nigeria and the results shows that the (MGM(1,1,⊗b)) model gives a prediction interval which the actual value is bracketed. This implies that natural gas consumption of Nigeria for 2021 to 2025 lies within the (MGM(1,1,⊗b)) model prediction values for the same year.